Repression of NF-κB impairs HeLa cell proliferation by functional interference with cell cycle checkpoint regulators - Kaltschmidt, Barbara; Dröge, Wulf (Oncogene, 1999)
NF-κB is an inducible transcription factor, which is regulated by interaction with inhibitory IκB proteins. Previous studies linked the activity of NF-κB to the proliferative state of the cell. Here we have analysed the function of NF-κB in the cell cycle. Inhibition of NF-κB in HeLa cells by stable overexpression of a transdominant negative IκB-α protein reduced cell growth. A kinetic analysis of the cell cycle revealed a retarded G1/S transition. The IκB-α overexpressing cell clones showed a decreased percentage of cells in the S phase and an impaired incorporation of bromodeoxyuridine (BrdU). The amounts of cyclins A, B1, D1, D3, and E were unchanged, but the G1-specific proteins cyclin D2 and cdk2 were strongly elevated in the IκB-α overexpressing cell clones. These cell clones also displayed an increase in cyclin D1-dependent kinase activity, pointing to a cell cycle arrest at the late G1 phase. IκB-α overexpression crosstalked to cell cycle checkpoints via a reduction of transcription factor p53 and elevation of p21WAF. Surprisingly, the IκB-α overexpressing cells showed an enrichment of c-Myc in the nucleoli, although the total amount of c-Myc protein was unchanged. These experiments identify an important contribution of the NF-κB/IκB system for the growth of HeLa cells.
Gesehen am 09.02.2021